Impacto da sucata ferrosa em qualidade, sustentabilidade e custos: estudo de caso do aço ferramenta H13 - Pereira, Mariana Santos (Universidade Federal de São Carlos, 2025)
Steel is one of the most important engineering materials in the world, serving as the foundation for the development of societies and nations, but it is also responsible for a significant share of global Greenhouse Gas (GHG) emissions. With the advent of Electric Arc Furnace steelmaking, it became possible to use ferrous scrap as a raw material on a larger scale, enabling greater circular economy practices. The growing demand for this raw material makes it necessary to discuss the relationship between availability and quality, since scrap comes from different sources and can undergo various separation and classification processes. The present work aims to study the impacts of using ferrous scrap in steels such as H13 produced via electric melting, in terms of raw material quality, product quality, sustainability indicators, and costs. For this analysis, a case study was conducted on a surface defect in H13 tool steel bars produced at Villares Metals. Samples of these steel bars were analyzed by optical microscopy and an electron probe micro-analyzer to characterize the defect, and absorbed impact energy data from the Charpy-V test were also examined. A comparative study was carried out on energy consumption and GHG emission indicators for eight companies in the steel industry, followed by an evaluation of possible scrap utilization scenarios and their impact in terms of scope 3 emissions. Finally, an economic comparison was made for the same scenarios, assessing the cost differences related to alternative raw materials that could replace ferrous scrap in H13 steel production. It can be stated that scrap quality directly affects product quality, potentially leading to defects such as hot shortness in H13 tool steels. It was also found that the electricity grid mix of the regions where the plants are located strongly influences emissions, and that the use of one ton of scrap can reduce emissions by up to 1.87 t CO₂eq. In the economic scenario, savings of up to BRL 2,491.00 per ton of product were observed when using scrap.
Impact of ferrous scrap on quality, sustainability, and costs: a case study of H13 tool steel
Keywords: Sucata ferrosa; Aço ferramenta H13; Sustentabilidade; Qualidade; Reciclagem; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA DE TRANSFORMACAO